Pathogenesis and Phylogenetic Analyses of Two Avian Influenza H7N1 Viruses Isolated from Wild Birds - Jin, Hongmei; Wang, Deli; Sun, Jing; Cui, Yanfang; Chen, Guang; Zhang, Xiaolin; Zhang, Jiajie; Li, Xiang; Chai, Hongliang; Gao, Yuwei; Li, Yanbing; Hua, Yuping (Frontiers in Microbiology, 2016)
Abstract: The emergence of human infections with a novel H7N9 influenza strain has raised global concerns about a potential human pandemic. To further understand the character of other influenza viruses of the H7 subtype, we selected two H7N1 avian influenza viruses (AIVs) isolated from wild birds during routine surveillance in China: A/Baer's Pochard/Hunan/414/2010 (BP/HuN/414/10) (H7N1) and A/Common Pochard/Xianghai/420/2010 (CP/XH/420/10) (H7N1). To better understand the molecular characteristics of these two isolated H7N1 viruses, we sequenced and phylogenetically analyzed their entire genomes. The results showed that the two H7N1 strains belonged to a Eurasian branch, originating from a common ancestor. Phylogenetic analysis of their hemagglutinin (HA) genes showed that BP/HuN/414/10 and CP/XH/420/10 have a more distant genetic relationship with A/Shanghai/13/2013 (H7N9), with similarities of 91.6% and 91.4%, respectively. To assess the replication and pathogenicity of these viruses in different hosts, they were inoculated in chickens, ducks and mice. Although both CP/XH/420/10 and BP/HuN/414/10 can infect chickens, ducks and mice, they exhibited different replication capacities in these animals. The results of this study demonstrated that two low pathogenic avian influenza (LPAI) H7N1 viruses of the Eurasian branch could infect mammals and may even have the potential to infect humans. Therefore, it is important to monitor H7 viruses in both domestic and wild birds.